p-Synephrine, the main protoalkaloid of Citrus aurantium, raises fat oxidation during exercise in elite cyclists - Gutiérrez-Hellin, J.; Baltazar-Martins, G.; Rodriguez, I.; Lara, B.; Ruiz-Moreno, C.; Aguilar-Navarro, M.; Del Coso, J. (European Journal of Sport Science, 2021)
Purpose: The aim of this study was to investigate the acute effects of p-synephrine ingestion on substrate oxidation during exercise in elite cyclists. Methods: Fifteen elite cyclists volunteered to participate in a double blind, crossover, randomized and placebo-controlled experimental trial. During two different trials, participants either ingested a placebo (cellulose) or 3 mg/kg of p-synephrine. After 60 min for substances absorption, participants performed an incremental maximal cycle ergometer test until volitional fatigue (25 W/min). Breath-by-breath gas exchange data was continuously recorded during the entire test to estimate energy expenditure, carbohydrate oxidation, and fat oxidation rates by stoichiometric equations. Heart rate was continuously measured by using a heart rate monitor. Results: The ingestion of p-synephrine had no significant effects on energy expenditure (F=0.71, P=0.40) or heart rate (F=0.66, P=0.43) during exercise. However, there was a main effect of p-synephrine to increase the rate of fat oxidation over the placebo (F=5.1, P=0.04) and the rate of fat oxidation was higher with p-synephrine in the following loads: 45±2%, 51±3%, 62±3%, 67±4%, 79±5% and 85±5% of the maximum wattage obtained in the test (all P<0.05). The ingestion of p-synephrine did not modify the maximal rate of fat oxidation during the ramp test (mean value; 95%CI = 0.91; 0.79-1.03 vs 1.01; 0.91-1.11 g/min, respectively, P=0.06) nor the exercise intensity at which maximal fat oxidation was achieved (i.e., Fatmax= 49; 48-53 vs 50; 47-51% Wmax, P=0.52). Conclusion: Acute p-synephrine ingestion moved the fat oxidation-exercise intensity curve upwards during an incremental cycling test without affecting Fatmax.